1999
DOI: 10.1143/jjap.38.7109
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculation of Photoabsorption of Various Polymers in an Extreme Ultraviolet Region

Abstract: We have calculated the linear absorption coefficients of various resist polymers using the mass absorption coefficients at 13 nm and the density obtained from the graph-theoretical treatment derived by Bicerano. The values indicate that the transmittance at 13 nm of conventional resists used in 193-nm, 248-nm and 365-nm lithography is about 30% when the thickness is 3000 Å and 60–70% when it is 1000 Å. This shows that conventional resists are suitable for an EUVL (extreme ultraviole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 8 publications
0
31
0
2
Order By: Relevance
“…The relative concentration of photoacid, H, after exposure is related to the unreacted photoacid generator by the equation m H − = 1 (6) Next, the acid deblocks the polymer resin during PEB. This is described by a reaction-diffusion model, given by ( )…”
Section: Governing Equations For Simplified and Full Resist Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative concentration of photoacid, H, after exposure is related to the unreacted photoacid generator by the equation m H − = 1 (6) Next, the acid deblocks the polymer resin during PEB. This is described by a reaction-diffusion model, given by ( )…”
Section: Governing Equations For Simplified and Full Resist Modelsmentioning
confidence: 99%
“…It is useful to examine a few examples of each of the different types of photoresist models commonly used by lithographers today. Molecular-scale models of the photoresist include dynamic Monte-Carlo [2], molecular dynamics [3,4], and ab initio quantum calculations [5][6][7]. These models are useful for developing a deeper understanding of resist chemistry and physics from a molecular standpoint, and these models can be used to examine new resist formulations.…”
Section: Introductionmentioning
confidence: 99%
“…In these previous works, acetal moieties showed higher sensitivity. Furthermore, Matsuzawa et al [11] examined the relationships between the resist properties and physical properties of various resist materials based on polymers and reported that lower-density polymers are more transparent and would also show higher sensitivity in the photoresist system.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption coefficient of a typical chemically amplified resist used in KrF excimer lithography is approximately 4 m -1 for 13.5 nm EUV. [1,2] For their use for KrF excimer lithography, the absorption coefficient of resists has generally been adjusted to less than 1 m -1 . Therefore, the strong absorption of EUV has been a concern because it may cause severe degradation of the resist sidewall.…”
Section: Introductionmentioning
confidence: 99%